Short-Term Outcomes and Clinical Efficacy of Stereotactic Body Radiation Therapy (SBRT) for Oligometastases of Prostate Cancer in China - Xu, Chenyang; Zhao, Xianzhi; Ju, Xiaoping; Shen, Yuxin; Qu, Min; Ye, Yusheng; Wang, Xiaoyan; Yu, Chunshan; Gao, Xu; Zhang, Huojun (Frontiers in Oncology, 2022)
Objective To assess the efficacy and safety of stereotactic body radiation therapy (SBRT) in managing oligometastases of prostate cancer. Moreover, it is the largest-to-date study in China to report the safety and efficacy of SBRT by CyberKnife for oligometastases of prostate cancer. Methods In this retrospective study, 75 patients with 108 oligometastases were treated by SBRT from May, 2012 to February, 2021. Among these patients, 43 patients were treated with the intention to control all known metastatic lesions and 32 were treated for palliative care. Patients received regular follow-up evaluation every 3 months. Efficacy was assessed based on local control (LC) rates, biochemical progression free survival (bPFS), progression free survival (PFS) and overall survival (OS). Safety was assessed based on clinical adverse events. Results Median follow-up time was 23.2 months (1.2-106.9 months). The complete response (CR), partial response (PR), stable disease (SD) and progressive disease (PD) rates were 63.0%, 10.2%, 21.3% and 5.6% respectively. The 6-month, 1, and 2-year LC rates were 100%, 97.5%, and 96.0% respectively while the 6-month, 1, and 2-year bPFS rates were 74.6 %, 53.3%, and 47.9%, respectively. Additionally, 6-month, 1, and 2-year PFS rates were 77.5%, 50.8%, and 47.2%, respectively. The 6-month, 1, and 2-year OS rates were 97.0%, 88.8%, and 87.0%, respectively. For the 15 metastatic castration-resistant prostate cancer (mCRPC) patients with 23 lesions, the 2-year LC rates were 93.8% while for 60 metastatic hormone-sensitive prostate cancer (mHSPC) patients with 85 lesions, the 2-year LC rates were 96.7%. No predictors of LC were found after univariate analysis. In those not on androgen deprivation therapy (ADT; n = 27), the 2-year freedom from ADT was 44.0%. All of the 24 patients with oligmetastase-induced complications experienced varying degrees of alleviation after SBRT. The treatment was well tolerated. No grade 3 or higher toxicity was observed. Conclusion SBRT is a safe and effective treatment modality in the management of oligometastases of mHSPC and mCRPC with high LC rates and acceptable toxicity. SBRT could provide treatment choice for mCRPC, as well as an alternative to delay the start of ADT for mHSPC.